Electrolytes disturbances in cancer patients. Issue 5 (18th September 2022) - Turcotte, Anna; Achi, Sai; Mamlouk, Omar; Mandayam, Sreedhar
Abstract : Purpose of review: Hypernatremia, hyperphosphatemia, hypocalcaemia, hyperkalaemia and hypermagnesemia are electrolytes disturbances that can arise in cancer patients in relation to unique causes that are related to the cancer itself or its treatment and can lead to delay or interruption of cancer therapy. This article summarizes these main causes, the proposed pathophysiology and the recommended management for these disturbances. Recent findings: There have been many cancer drugs approved in the field of oncology over the past several years and a subset of these drugs have been associated with electrolytes disturbances. This includes, for example, immune checkpoint inhibitor related hyperkalemia, fibroblast growth factor 23 inhibitor associated hyperphosphatemia and epidermal growth factor receptor inhibitor associated hypomagnesemia and hypocalcaemia. Summary: This article provides an updated review of certain electrolytes disturbance in cancer patients and allows clinicians to have a greater awareness and knowledge of these electrolyte abnormalities in efforts to early recognition and timely management.